Abduction and asylum in the lives of transcription factors - Burger, Anat (National Academy of Sciences, 2010)
Recent studies suggest that there are many nonfunctional transcription factor binding sites along a genome. Although these “decoy” sites compete with the promoter region for binding of transcription factors, they may also protect these proteins from degradation. We show that in the limit of perfect protection, where bound transcription factors are never degraded, the competitive effect of nonfunctional binding sites is completely canceled out by the stability gained from reduced degradation. We examine the response of an autoregulated gene to the total number of transcription factors to quantify the consequences of competition for transcription factors. We show that intuition about this system can be gained by mathematically constructing a single gene with effective parameters that reproduce the behavior of a gene with added decoy sites. In analogy to dressed particles in many-body systems we term this description a “quasi gene.” We find that protective decoys buffer against noise by reducing correlations between transcription factors, specifically in the case of production of transcription factors in bursts. We show that the addition of protective decoy sites causes the level of gene expression to approach that predicted from deterministic mass action models. Finally, we show that protective decoy sites decrease the size of the region of parameter space that exhibits bistability.